Effects of six-week stroboscopic training program on visuomotor reaction speed in goal-directed movements in young volleyball players: a study focusing on agility performance - Zwierko, M.; Jedziniak, W.; Popowczak, M.; Rokita, A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background In team sports, deficits in visuomotor reaction speed are considered a significant and modifiable risk factor that can lead to decreased performance and an increased risk of injuries. Thus, identifying effective methods to enhance visuomotor abilities is crucial. The main objective of this research was to investigate the impact of a six-week stroboscopic intervention on visuomotor reaction speed in goal-directed specific movements based on agility among young volleyball players. Additionally, the study aimed to explore the impact of saccade dynamics on visuomotor reaction speed performance throughout the experiment.